2020
DOI: 10.1002/acm2.12899
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of the output factor using machine and deep learning approach in uniform scanning proton therapy

Abstract: Purpose The purpose of this work is to develop machine and deep learning‐based models to predict output and MU based on measured patient quality assurance (QA) data in uniform scanning proton therapy (USPT). Methods This study involves 4,231 patient QA measurements conducted over the last 6 years. In the current approach, output and MU are predicted by an empirical model (EM) based on patient treatment plan parameters. In this study, two MATLAB‐based machine and deep le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…There is a clinical need for developing software to automatically run in the background to put the DQA data into a database and show each parameter trend with time. Few DQA literature combined the DQA data with automation and Artificial Intelligent (AI) implementation, 9 although there have been reports on machine learning applications in proton dose verifications, 10–12 Linac QA, 13–15 patient‐specific QA in radiotherapy 16–19 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a clinical need for developing software to automatically run in the background to put the DQA data into a database and show each parameter trend with time. Few DQA literature combined the DQA data with automation and Artificial Intelligent (AI) implementation, 9 although there have been reports on machine learning applications in proton dose verifications, 10–12 Linac QA, 13–15 patient‐specific QA in radiotherapy 16–19 …”
Section: Introductionmentioning
confidence: 99%
“…There is a clinical need for developing software to automatically run in the background to put the DQA data into a database and show each parameter trend with time. Few DQA literature combined the DQA data with automation and Artificial Intelligent (AI) implementation, 9 although there have been reports on machine learning applications in proton dose verifications, [10][11][12] Linac QA, [13][14][15] patient-specific QA in radiotherapy. [16][17][18][19] Based on the clinical urgent need for DQA procedures, automation, and AI implementation, an auto trending DQA program alignment with TG 224 guideline has been developed at New York Proton Center (NYPC).…”
mentioning
confidence: 99%
“…Note that there is another approach, where the output prediction was performed by machine learning. 21,22 But we chose to fit the data analytically because this is transparent and easy to handle. Even though the machine learning approach could give a better prediction than the conventional method, it is hard to understand the origin of the result due to its black-box nature.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that machine learning methods can be used for a sanity check of output measurements and has the potential to eliminate time-consuming patient-specific measurements. Similarly, Grewal et al utilized 4,231 QA measurements with a train/test split of 90 and 10% to build models to predict OF and MU for uniform scanning proton beams with two learning algorithms—Gaussian process regression and shallow neural network (Grewal et al, 2020 ). They found that the prediction accuracy of machine and deep learning algorithms is higher than the empirical model currently used in the clinic.…”
Section: Machine Learning Applications In Machine Qamentioning
confidence: 99%